What is the optimal treatment time for larval therapy? A study on incubation time and tissue debridement by bagged maggots of the greenbottle fly, Lucilia sericata. Issue 1 (31st October 2018) - Wilson, Michael R.; Nigam, Yamni; Knight, John; Pritchard, David I.
Abstract : The effective use of larvae of the greenbottle fly, Lucilia sericata, in wound debridement requires a working knowledge of how feeding changes over time. Using a laboratory assay and bagged larval dressings, the effect of incubation time on larval feeding rates and body mass was investigated for up to 120 hours at 32°C. The mass of tissue digested increased significantly in incremental 24‐hour periods up to 72 hours, with no significant consumption occurring afterwards. Larval mass increased only up to 48 hours. A further test comparing the efficacy of a single 96‐hour application of larvae against two consecutive 48‐hour applications found that the mass of tissue digested in the latter was 14.3% higher than the former, a difference that was statistically significant. Current clinical guidance suggests a 4‐day application period for bagged larvae. Based on these results, an incubation time of 72 hours (3 days) for bagged larvae would be the most effective at the study temperature. However, it is acknowledged that wound temperature can vary, whereby feeding rates would likely differ. In view of this, we conclude that a period of 3 to 4 days is optimum for the application of larvae, and current guidelines should be adhered to.